A study on workability measurement and correlation with performance of hot mix asphalt / Salah Mohamed Khalil Abdelgalil - Abdelgalil, Salah Mohamed Khalil (Institute of Graduate Studies, UiTM, 2014)
The difficulty in obtaining the required density and smoothness of constructed pavement, establishing conformity between registered process input parameter and tested output of asphaltic concrete; couple with the effect of small change in aggregate gradation on the workability of asphaltic concrete just as inadequate compaction can result to moisture induced damage are the main factors that triggers this research. The research was therefore undertaken to improve means of measuring workability. The research was divided into three tasks. Task one was consideration of all the materials used in the research. Task two was undertaken to achieve the first objective which is development of an improved workability measuring device. The components were designed, fabricated and a suitable transducer was incorporated. In order to obtain the best paddle suitable for the device out of three types paddle configurations named A, B and C. Seven types of mixes were designed in accordance with (PWD) Malaysia’s specifications for road works.